Hot‐Spot Engineering in 3D Multi‐Branched Nanostructures: Ultrasensitive Substrates for Surface‐Enhanced Raman Spectroscopy. Issue 4 (30th January 2017) - Chirumamilla, Manohar; Chirumamilla, Anisha; Roberts, Alexander S.; Zaccaria, Remo Proietti; De Angelis, Francesco; Kjær Kristensen, Peter; Krahne, Roman; Bozhevolnyi, Sergey I.; Pedersen, Kjeld; Toma, Andrea
Abstract : The detection of probe molecules at ultralow concentrations, even at the single‐molecule level, can be addressed with the breakthrough concept of plasmonic hot‐spot engineering. In view of that, the fabrication of nanostructures endowed with sub‐10 nm gaps and extremely large near‐field enhancement has gained increasing attention, becoming a key‐condition for improved sensitivity. The present work demonstrates a new perspective in ultrasensitive detection by engineering every individual plasmonic nanostructure with a giant electric field confinement and superior hot‐spot densities, thus eliminating the need for extremely narrow interparticle separations. Abstract : Novel 3D multi‐branched nanostars are implemented to demonstrate ultrasensitive surface‐enhanced Raman scattering. Every individual plasmonic nanostructure is engineered with high hot‐spot densities and extremely large near‐field enhancement. Ultrasensitive detection of p‐Aminothiophenol and Rhodamine‐6G chemisorbed from solutions at 1 fM concentration is achieved.